2005
DOI: 10.1007/bf03016530
|View full text |Cite
|
Sign up to set email alerts
|

Systemic ketamine inhibits hypersensitivity after surgery via descending inhibitory pathways in rats

Abstract: P Pu ur rp po os se e: : Systemic ketamine suppresses several types of chronic pain. Although ketamine is used as a general anesthetic agent, the analgesic effect of systemic ketamine for early-stage postoperative pain is not clear. We investigated the efficacy and mechanism of systemic ketamine in a rat model of postoperative pain.M Me et th ho od ds s: : An incision was made in the plantar aspect of the left hind paw in male Wistar rats. Mechanical hypersensitivity was measured using calibrated von Frey fila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
41
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 36 publications
(53 reference statements)
5
41
0
1
Order By: Relevance
“…32-34 At 10mg/kg ketamine is known to treat depression 38 without causing psychomotor side-effects. 27,41 We observed statistically significant relief of depression beginning one day after ketamine administration and lasting 5 days. Therefore, at this dose ketamine appeared to illustrate a distinction between the sensory and affective responses to pain.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…32-34 At 10mg/kg ketamine is known to treat depression 38 without causing psychomotor side-effects. 27,41 We observed statistically significant relief of depression beginning one day after ketamine administration and lasting 5 days. Therefore, at this dose ketamine appeared to illustrate a distinction between the sensory and affective responses to pain.…”
Section: Discussionmentioning
confidence: 64%
“…40-42 The duration of anti-nociception is also variable, but most often limited to within 24 hrs. 27,41 It is possible that ketamine relieved spontaneous pain at low doses, but higher doses are required to treat evoked pain (tested by mechanical and cold hypersensitivities). However, even at higher doses of ketamine (20 and 50 mg/kg), there was no relief of evoked pain 24 hr after administration (fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although i.t. NMDA receptor antagonists have been typically described as antinociceptive, on closer evaluation, the degree of antinociception is highly dependent on the compound, injury state and the tested sensory modality (Bennett et al, 2000a; Chaplan et al, 1997; Koizuka et al, 2005; Mao et al, 1993). Chaplan et al (1997) found no significant antinociceptive effect of ketamine in nerve-injured rats and a MPE of less than 50% for MK-801.…”
Section: Discussionmentioning
confidence: 99%